Spurious Asthma Presentation during COVID-19 - Israel Amirav; Moran Lavie (MDPI AG, 2021)
The use of face masks as a means for preventing the spread of SARS-CoV-2 is now a common practice world-wide. Three children presented to our specialty clinic with respiratory complaints during protective face mask wearing. They were diagnosed as asthma and referred to our specialist clinic for further evaluation after asthma treatments were ineffective. Full details and a video clip demonstrating the effects of wearing the mask is presented for the first patient. The detailed evaluation confirmed the diagnosis of hyperventilation. Conclusions: In the current era of the daily use of masks, pediatricians should be aware of potential anxiety and hyperventilation while the mask is being worn, causing symptoms that mimic common respiratory disorders, such as asthma.